Direitos humanos da pessoa com deficiência: percepção de mães e pais cuidadores - Spini, Marta Rezende (2016)
The issue of human rights of people with disabilities has been the interest of many current studies. This research has as main topic the caregiver of children with disabilities. In this point of view, this study aims to describe and analyze the knowledge of parents about the rights of children with disabilities and if this knowledge provides their empowerment and strengthening it in the daily care of their child. The analysis was based on a qualitative perspective into social constructionism and was organized from three categories: a) Invisibility in visible; b) My, yours, our right; c) collective rights. The social constructionism provides an invitation to dialogue, legitimizing and encouraging the understanding of the interviewed. The methodological reference was guided into the qualitative approach and the constructionist assumptions. The participants are parents of disabled children of 0-6 years old, attending three institutions in Itumbiara, Goiás: APAE, AMA and NAPEO. The choice of the period 0-6 years old was due to changes and acquisitions that occur in children overall development period. The caregivers participated in a semistructured interview and a focus group, in which were discussed the human rights, about children with disabilities and care. The data analysis was guided by social constructionist proposal supported by extensive reading of the transcribed interviews and analysis of issues raised from this material. The categories afforded by the caregiver's relationship with their family, the various institutions attending the children and society as a whole allowed to demonstrate an awareness about the care and necessary changes from the understanding of human rights. The need to create mechanisms and strategies in which the family participates as an active voice and able to mobilize changes emerged as need for contextualized care forms involving multidisciplinary and interdisciplinary teams and extended networks. In view of this, arises the question about from which place the caregiver can speak from his experiences in seeking joint solutions with the society.